MANAGEMENT OF DAKWAH ACTIVITIES BY THE MIFTAHUL JANNAH TAKLIM ASSEMBLY TO ENHANCE SOCIAL HARMONY IN BATANG TERAP VILLAGE, PERBAUNGAN DISTRICT - Febriani Manurung; Faridah Faridah (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2026)
The significance of effective da'wah management in supporting the development of harmonious family life within communities underpins this research. The Miftahul Jannah Taklim Assembly, a non-formal da'wah institution, conducts religious development activities that emphasize both enhancing religious understanding and strengthening family life among its congregation. This study investigates the da'wah management practices of the Miftahul Jannah Taklim Assembly in promoting family harmony in Batang Terap Village, Perbaungan District. A qualitative research method with a descriptive approach was employed. Data collection involved observation, interviews, and documentation, with research informants comprising the head of the taklim assembly and congregation members. Findings indicate that da'wah management at the Miftahul Jannah Taklim Assembly is operationalized through the functions of planning, organizing, implementing, and evaluating. Planning involves preparing schedules for religious studies and selecting materials relevant to the congregation's needs. Organization is achieved through the allocation of responsibilities among administrators. Da'wah activities are carried out via regular religious studies and social programs. Evaluation is conducted by monitoring attendance, participation, and observable changes in congregational attitudes. The implementation of these da'wah management practices has contributed positively to family harmony within the congregation, particularly by enhancing communication, patience, and relationships among family members.